Mediating Role of Customer Engagement: Brand Image Enhancement from Social-Media Marketing - Roymon Panjaitan (Jurnal Maksipreneur, 2022)
To be more competitive, the growth of the creative economy requires customer interaction. This necessitates the use of social media marketing as an efficient marketing platform for products or services based on the existing brand image. The purpose of this study was to examine the role of customer engagement in mediating brand image from relational social media marketing, as well as the role of brand image in mediating consumer engagement from relational social media marketing. The sampling approach is probability sampling, and the method is quantitative. With the sampling approach used, simple random sampling through the distribution of questionnaires, data was collected from 100 respondents. The results of the data analysis were then processed using SPSS 25 software. According to the findings of this investigation, the mediation function is important.